Scale of Adherence to Good Hospital Practices for COVID-19: Psychometric Properties - Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; Melchiades, Ediana Preisler [UNESP]; Ramos, Melissa Santiloni Montanha [UNESP]; de Morais, José Fausto; de Oliveira, Cesar (MDPI, 2022)
To avoid hospital transmission, all COVID-19 prevention measures should be followed. This study aimed to evaluate the psychometric properties of a novel scale developed to assess adherence to good practices for COVID-19 in the hospital setting. A methodological cross-sectional study was conducted at a public hospital in the state of São Paulo, Brazil, with 307 healthcare providers. Data were collected using a questionnaire addressing sociodemographic/occupational data and the Adherence to Standard Precautions for COVID-19 scale. Cronbach’s alpha coefficients and the intraclass correlation coefficients were used to measure internal consistency and temporal stability (test-retest analysis), respectively. Concurrent validity was evaluated using Spearman’s correlation coefficients between the scores of the overall scale and its domains. Factorial structure was evaluated using exploratory factor analysis and goodness-of-fit of the model was tested using confirmatory factor analysis. Cronbach’s alpha coefficients for the scale and its domains were higher than 0.7, except the psychosocial domain (0.61). All intraclass correlation coefficients were higher than 0.7. Strong correlations were found between the total score and the personal (0.84) and organizational (0.90) domains of the scale and a good correlation was found with the psychosocial domain (0.66). The fit of the multidimensional model was satisfactory for all parameters and the three-dimensional structure of the scale was confirmed by the fit of the factor loadings. The novel scale is a valid and reliable instrument for assessing adherence to good hospital practices for COVID-19.
Keywords: COVID-19; methodological study; psychometrics; validation study